A writer's topography : space and place in the life and works of Albert Camus - Herbeck, Jason; Grégoire, Vincent (Faux titre, 2015)
Albert Camus sustained a lifelong awareness of and appreciation for what he termed le visage de ce monde -the face of this earth. This original collection of essays examines how topography influenced Camus's understanding and expression of the human condition.